Restorative Justice and State Responsibility for the Return of Rights of Victims Due to Fraud in Indonesia - Amriyanto, Amriyanto; Syafari, Tri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The rise of fraudulent practices that end up in criminal acts and cause material losses to victims, for example the First Travel and Abu Tours cases in Indonesia, which have captured massive public attention, has shifted the orientation of punishment in criminal law, especially in property crimes from Lex Talionis towards Restitutio ad Integrum which emphasises restoration to the original state. This paper will analyse how the responsibility of the state and how the restorative justice approach in addressing the problem of fraud in Indonesia. The research method uses a normative legal research model with secondary data as analytical material. The results show that restitution and compensation instruments are an option in restoring victims of property crime. Restitution is the responsibility of the perpetrator to restore the victim, while compensation is the responsibility of the state as part of the state's role in realising the welfare of the people. Restorative justice as a means of resolving property crimes, especially fraud, offers an alternative that is oriented towards effective legal remedies to provide adequate legal protection for victims, although in practice there are still some fundamental changes.